Determinants of IPO Underpricing in the Energy Industry: Evidence from the US Market - Shaikh, Abdul Musawir (2012)
Given the volatile global economic conditions and extreme uncertainty surrounding the global capital markets, I study the recent theoretical developments of underpricing in IPO markets. Since previous literature has shown contradicting results on the tests of determinants of IPO underpricing, I expand on previous literature by testing some of the theories on the Energy industry specifically as the Energy industry is crucial to our economic development. Using US data from 1990-2011, I show that on average, stocks are underpriced in the Energy industry by 6.18%. Moreover, the 22 year sample period of Energy industry that I used shows that around $5.64 billion was left on the table due to underpricing. Furthermore, I prove the existence of Hot and Cold IPO markets in the Energy industry and also show that the size of the issue, standard deviation of stock returns and the reputation of the underwriter help explain the underpricing in the Energy industry. Previous literature has developed a negative relationship between the Offer price and underpricing, but my results show the contrary and the logical explanation for this has been given. Last, but not the least, I test a commodity return (Oil price) with underpricing levels but fail to find evidence of a relationship between the two.